2016
DOI: 10.1038/ncomms10659
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecapolar colloids

Abstract: Outermost occupied electron shells of chemical elements can have symmetries resembling that of monopoles, dipoles, quadrupoles and octupoles corresponding to filled s-, p-, d- and f-orbitals. Theoretically, elements with hexadecapolar outer shells could also exist, but none of the known elements have filled g-orbitals. On the other hand, the research paradigm of ‘colloidal atoms' displays complexity of particle behaviour exceeding that of atomic counterparts, which is driven by DNA functionalization, geometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 46 publications
6
75
0
Order By: Relevance
“…The leading-order multipoles are typically monopoles, dipoles, and quadrupoles, with higher-order multipoles rarely playing dominant roles, though we will see that they can be important for certain types of nematic colloids (2,(8)(9)(10)(11)(12)(13)(20)(21)(22)(23)(24). Much like in the case of electrostatic charge distributions, the far-field distortions of n(r) due to a colloidal particle can be represented as elastic multipoles (2,13,(20)(21)(22)(23)(24). Far from a colloidal particle, the deviations of the director n  (=x; y) from the far-field uniform director n 0 =(0, 0, 1) are small (24,25).…”
Section: Elastic Multipolesmentioning
confidence: 92%
See 3 more Smart Citations
“…The leading-order multipoles are typically monopoles, dipoles, and quadrupoles, with higher-order multipoles rarely playing dominant roles, though we will see that they can be important for certain types of nematic colloids (2,(8)(9)(10)(11)(12)(13)(20)(21)(22)(23)(24). Much like in the case of electrostatic charge distributions, the far-field distortions of n(r) due to a colloidal particle can be represented as elastic multipoles (2,13,(20)(21)(22)(23)(24). Far from a colloidal particle, the deviations of the director n  (=x; y) from the far-field uniform director n 0 =(0, 0, 1) are small (24,25).…”
Section: Elastic Multipolesmentioning
confidence: 92%
“…Much like in the case of electrostatic charge distributions, the far-field distortions of n(r) due to a colloidal particle can be represented as elastic multipoles (2,13,(20)(21)(22)(23)(24). Far from a colloidal particle, the deviations of the director n  (=x; y) from the far-field uniform director n 0 =(0, 0, 1) are small (24,25). Assuming one-elastic-constant approximation and representing the field as n(r)  (n x , n y , 1), the LC elastic free energy is expressed as…”
Section: Elastic Multipolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was reported that polystyrene colloidal particles can align the LC molecules at an oblique angle (conical degenerate anchoring) giving rise to a new type of LC colloids [31]. Here we restrict our study to homeotropic and planar degenerate anchorings.…”
Section: A Single Lock Particlementioning
confidence: 99%